1995
DOI: 10.1007/bf03011877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamic changes induced by sevoflurane and halothane in paediatric patients

Abstract: Comparison of haemodynamic changes induced by sevoflurane and halothane in paediatric patientsSevoflurane is used in paediatric anaesthesia 1,2 because of its small blood-gas partition coefficient (0.63), 3 which enables rapid induction of, and rapid emergence from anaesthesia. Paediatric patients have a relatively high minimum alveolar concentration (MAC) of volatile anaesthetics that may cause marked haemodynamic depression, especially in neonates and infants. 4-7 In mongrel dogs, sevoflurane decreases cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
(7 reference statements)
6
15
0
Order By: Relevance
“…At one to two minimum alveolar concentration (MAC) sevoflurane, HR was maintained or increased in infants and children who received no atropine, although SBP was depressed 20% to 25% from awake values [17][18][19]. Data from the present study similarly found that children without Down syndrome experienced a slight though nonsignificant increase in HR from baseline, yet a significant decrease in MAP during sevoflurane use.…”
Section: Discussionsupporting
confidence: 82%
“…At one to two minimum alveolar concentration (MAC) sevoflurane, HR was maintained or increased in infants and children who received no atropine, although SBP was depressed 20% to 25% from awake values [17][18][19]. Data from the present study similarly found that children without Down syndrome experienced a slight though nonsignificant increase in HR from baseline, yet a significant decrease in MAP during sevoflurane use.…”
Section: Discussionsupporting
confidence: 82%
“…[33,[42][43][44][45]49] The decreases were smaller than with desflurane, [51] similar to those with isoflurane [45] and generally similar to [49] or significantly lower [44] than with halothane. Changes in blood pressure and the incidence of hypotension (≥30% decrease in systolic blood pressure) were inversely related to age (the study included neonates aged ≤30 days and children aged 0.5 to 12 years).…”
Section: Other Effects (Contd)supporting
confidence: 50%
“…[1] In 38 children (aged 1 to 6 years), equipotent doses of the 2 agents (with 100% oxygen) caused a significant reduction in stroke volume index but only slight nonsignificant decreases in cardiac index. [43] Cardiac index significantly decreased from awake values in 15 halothane-but not 15 sevoflurane-treated infants (mean age about 6 months) receiving equipotent doses of the drugs with N 2 O 50% (p < 0.05 for halothane vs sevoflurane also). [49] Halothane had a significantly greater depressant effect on most indices of contractility than sevoflurane in this [49] and another trial in 20 children.…”
Section: Other Effects (Contd)mentioning
confidence: 94%
See 1 more Smart Citation
“…Friesen R H et al (1982), 13 Epstein R H et al (1995), 14 Sarner J B et al (1995), 11 Shin Kawana et al (1995), 15 Black A et al (1996), 7 Brien K O et al (1998), 5 and H Vitanen (1999) 16 have studied mean arterial pressure during induction and after intubation under Sevoflurane and Halothane anaesthesia. In the present study, in group H, mean systolic blood pressure and mean arterial pressure decreased during intubation by 10 mm of Hg and increased after intubation.…”
Section: Mean Arterial Pressurementioning
confidence: 99%